Pengaruh kemanjuran-diri terhadap tingkah laku innovatif di kalangan pekerja-pekerja peringkat eksekutif di syarikat multinasional asing yang beroperasi di Malaysia - Ahmad, Fakhrorazi; Husin, Hartini; Nik Abdullah, Nik Ab. Halim (2016)
[Effect of Self-Efficacy on Innovative Behaviors Among Employees of the Executive Level in Foreign Multinational Companies Operating in Malaysia] Elements of self-efficacy, better known as self-efficacy in English is a very important element of motivation in influencing a person's behavior, such as what has been stated in the social cognitive theory.To evaluate the effect of self-efficacy to innovative behavior, a detailed study has been carried out in some selected companies in the country.The companies involved are foreign multinational companies operating in Malaysia in the electrical and electronics sector.A total of 304 respondents from various companies and backgrounds from all over Malaysia have responded to the questions of the questionnaire that was circulated. Data were then analyzed directly by using the variance-based SEM with Smart-PLS v2 program.The study found that self-efficacy huge impact on the innovative behavior of employees. This finding is also consistent with the statement in the social cognitive theory.In conclusion, to drive innovative behavior among employees to a higher level in the organization, the level of self-efficacy for each employee should be enhanced.If necessary, specific training related self-efficacy should be given to every employee in an organization.